RETRACTED ARTICLE: MicroRNA-206 inhibition and activation of the AMPK/Nampt signalling pathway enhance sevoflurane post-conditioning-induced amelioration of myocardial ischaemia/reperfusion injury. (2nd January 2020) - Li, Tao; Yu, Shan-Shan; Zhou, Chang-Yu; Wang, Ke; Wan, Ying-Chun
Abstract: We, the Editor and Publishers of Journal of Drug Targeting, have retracted the following article: Tao Li, Shan-Shan Yu, Chang-Yu Zhou, Ke Wang, Ying-Chun Wan. MicroRNA-206 inhibition and activation of the AMPK/Nampt signalling pathway enhance sevoflurane post-conditioning-induced amelioration of myocardial ischaemia/reperfusion injury. J Drug Target. 2019;28(1):80–91. DOI: 10.1080/1061186X.2019.1616744 Following publication, concerns were raised regarding the alleged duplication of images in Figure 3A in which regions of panel SP + miR-206 inhibitor appeared to be duplicated with regions of panel SP + AICAR. The authors did not respond to our queries and were unable to provide their original data or any necessary supporting information. As verifying the validity of published work is core to the integrity of the scholarly record, we are therefore retracting the article. All authors listed in this publication have been informed of this decision. We have been informed in our decision-making by our policy on publishing ethics and integrity and the COPE guidelines on retractions. The retracted article will remain online to maintain the scholarly record, but it will be digitally watermarked on each page as 'Retracted'.